2018
DOI: 10.3390/min8090368
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Configurations of Lead(II)-Benzohydroxamic Acid Coordination Compounds in Aqueous Solution: A Combined Experimental and Computational Study

Abstract: Novel collector lead(II)-benzohydroxamic acid (Pb(II)–BHA) complexes in aqueous solution were characterized by using experimental approaches, including Ultraviolet-visible (UV-Vis) spectroscopy and electrospray ionization-mass spectrometry (ESI-MS), as well as first-principle density functional theory (DFT) calculations with consideration for solvation effects. The Job plot delineated that a single coordinated Pb(BHA)+ should be formed first, and that the higher coordination number complexes can be formed subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Flotation is one of the most efficient methods to purify useful minerals from the complex raw ores based on the distinct surface hydrophobicity of minerals. In the flotation system, metal ions are conventionally pre-added as activators to alter the surface, which means that metal ions are pre-adsorbed on the surface and restricted on the surface. Flotation reagents are subsequently added to alter the surface hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flotation is one of the most efficient methods to purify useful minerals from the complex raw ores based on the distinct surface hydrophobicity of minerals. In the flotation system, metal ions are conventionally pre-added as activators to alter the surface, which means that metal ions are pre-adsorbed on the surface and restricted on the surface. Flotation reagents are subsequently added to alter the surface hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Flotation reagents are subsequently added to alter the surface hydrophobicity. Collectors such as hydroxamic acids (HAs) bearing reagents can interact with metal ions such as Cu 2+ , Cd 2+ , Co 2+ , Ni 2+ , Pb 2+ , Zn 2+ , and Fe 3+ , thus taking on abundant chelate structures at the mineral surface via surface coordination. , It has been reported that the lead ion (Pb 2+ ) with benzohydroxamic acid (BHA), salicylhydroxamic acid (SHA), and cupferron can enhance the selectivity of flotation performance of the metal oxide minerals. However, the understanding of their surface coordination structure and mechanism is still lacking …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published articles can be analyzed following the same scale logic. Molecular modeling has allowed for an improved understanding of the mechanisms of interaction between minerals, the aqueous medium, and flotation reagents [13][14][15]. For example, studies on the behavior and molecular mechanism of adsorption of the collector sodium oleate were carried out by density functional theory and experimental techniques [13].…”
mentioning
confidence: 99%
“…Density functional theory is one of the most used methods in quantum calculations of the electronic structure of matter. Usually, functional density theory is combined with experimental studies; for example, molecular modeling helps identify the most stable structure of ionic species and identify active sites, while experimental techniques such as electrospray ionization-mass spectrometry and ultraviolet-visible spectroscopy allow the existence of molecules or complexes to be validated qualitatively and quantitatively [15]. These three manuscripts are good examples of the useful tool that molecular modeling can be for understanding the performance and development of new reagents.…”
mentioning
confidence: 99%